Long short‐term memory and convolutional neural network for abnormal driving behaviour recognition. Issue 5 (24th July 2019) - Jia, Shuo; Hui, Fei; Li, Shining; Zhao, Xiangmo; Khattak, Asad J.
Abstract : Abnormal driving behaviours, such as rapid acceleration, emergency braking, and rapid lane changing, bring great uncertainty to traffic, and can easily lead to traffic accidents. The accurate identification of abnormal driving behaviour helps to judge the driver's driving style, inform surrounding vehicles, and ensure the road traffic safety. Most of the existing studies use clustering and shallow learning, it is difficult to accurately identify the types of abnormal driving behaviours. Aimed at addressing the difficulty of identifying driving behaviour, this study proposed a recognition model based on a long short‐term memory network and convolutional neural network (LSTM‐CNN). The extreme acceleration and deceleration points are detected through the statistical analysis of real vehicle driving data, and the driving behaviour recognition data set is established. By using the data set to train the model, the LSTM‐CNN can achieve a better result.